Emulsion-based systems for delivery of food active compounds : formation, application, health and safety - Roohinejad, Shahin; Greiner, Ralf; Oey, Inwati; Wen, Jingyuan (John Wiley & Sons, Inc., 2018)
A comprehensive text that offers a review of the delivery of food active compounds through emulsion-based systems Emulsion-based Systems for Delivery of Food Active Compounds is a comprehensive recourse that reviews the principles of emulsion-based systems formation, examines their characterization and explores their effective application as carriers for delivery of food active ingredients. The text also includes information on emulsion-based systems in regards to digestibility and health and safety challenges for use in food systems. Each chapter reviews specific emulsion-based systems (Pickering, multiple, multilayered, solid lipid nanoparticles, nanostructured lipid carriers and more) and explains their application for delivery of food active compounds used in food systems. In addition, the authors ' noted experts in the field ' review the biological fate, bioavailability and the health and safety challenges of using emulsion-based systems as carriers for delivery of food active compounds in food systems. This important resource: -Offers a comprehensive text that includes detailed coverage of emulsion-based systems for the delivery of food active compounds -Presents the most recent development in emulsion-based systems that are among the most widely-used delivery systems developed to control the release of food active compounds -Includes a guide for industrial applications for example food and drug delivery is a key concern for the food and pharmaceutical industries Emulsion-based Systems for Delivery of Food Active Compounds is designed for food scientists as well as those working in the food, nutraceutical and pharmaceutical and beverage industries. The text offers a comprehensive review of the essential elements of emulsion-based systems for delivery of food active compounds.- Resumé vydavatel
Keywords: potravinářství; emulze; biologicky aktivní látky; food industry and trade; bioactive compounds; emulsions; elektronické knihy; sborníky; electronic books; papers of several authors